Imperatives of Public Administration in Processes of Optimization of Executive Authorities - Yarmystiy, Maksym (Pressing Problems of Public Administration, 2024)
The article examines the imperatives of public administration in the context of ensuring improvement of the activities of executive authorities. The author analyses the works of Ukrainian scholars on imperatives in various areas of management activity and establishes, in particular, that there is no unified approach to determining the content and nominations (types) of imperatives in the public administration system. The author proposes a classification of public administration imperatives aimed at increasing managerial capacity and affecting the efficiency of executive bodies. Attention is focused on four imperatives of public administration: institutional, administrative, generative and interactive. Each of the imperatives is responsible for the development of relevant locations or components of management activities in executive bodies. The author establishes that the main condition for ensuring the efficiency of executive authorities is the application of an integrated approach to solving problematic issues at all locations of public administration. The question of the place and role of public administration imperatives in the global processes of the world order remains important. Therefore, along with the generally accepted imperatives of global development, it is advisable to take into account the imperatives of public administration both for the development of executive authorities in a particular country and in the countries of the respective continent.